Pattern‐based GUI testing: Bridging the gap between design and quality assurance. (2nd March 2017) - Moreira, Rodrigo M. L. M.; Paiva, Ana Cristina; Nabuco, Miguel; Memon, Atif
Summary: Software systems with a graphical user interface (GUI) front end are typically designed using user interface (UI) Patterns, which describe generic solutions (with multiple possible implementations) for recurrent GUI design problems. However, existing testing techniques do not take advantage of this fact to test GUIs more efficiently. In this paper, we present a new pattern‐based GUI testing (PBGT) approach that formalizes the notion of UI Test Patterns, which are generic test strategies to test UI patterns over their different implementations. The PBGT approach is evaluated via 2 case studies. The first study involves 2 fielded Web application subjects; findings show that PBGT is both practical and useful, as testing teams were able to find real bugs in a reasonable time interval. The second study allows deeper analysis by studying software subjects seeded with artificial faults; the findings show that PBGT is more effective than a manual model‐based test case generation approach. Abstract : Pattern‐based graphical user interface testing, a practical and useful model‐based graphical user interface testing approach that allows to find fast real bugs in the software and is more effective than a manual model‐based test case generation approach.